Alternative entropies and consistent black hole thermodynamics - Nojiri, Shin’ichi; Odintsov, Sergei D.; Faraoni, Valerio (International journal of geometric methods in modern physics, 2022)
While the Bekenstein–Hawking entropy is the unique notion of entropy that makes classical black hole thermodynamics consistent, alternative entropy notions (Rényi, Tsallis, and generalized constructs) abound in the literature. We explore conditions under which they are part of a consistent horizon thermodynamics for certain classes of modified gravity black holes. We provide examples in which black hole masses and temperatures going hand-in-hand with these alternative entropies coincide with their usual counterparts associated with the Bekenstein–Hawking entropy.